BEYOND HEROES AND VILLAINS: PORTRAYAL OF HEALTHCARE WORKERS IN FILM “VIRUS” - C, Anaina; Gouda, Nikhil Kumar; Patnaik, Sudhir Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The portrayal of healthcare workers in films significantly influences public perception. This study delves into the Malayalam film "Virus," a dramatization of the 2018 Nipah virus outbreak in Kerala, India. Using a semiotic approach, it investigates the representation of healthcare workers through visual elements, character traits, and interactions within the film. Rather than resorting to clichéd depictions of heroic saviors` or villainous doctors, "Virus" offers a nuanced and realistic portrayal. The analysis scrutinizes how healthcare workers are visually depicted through clothing, body language, and facial expressions, reflecting their dedication, expertise, and resilience. It delves into the film's portrayal of character traits, emphasizing their unwavering commitment despite facing significant personal risk and exposure to a deadly virus. Furthermore, it examines how their interactions with patients and authorities illustrate the challenges they confront during a public health crisis. By dissecting these signs and symbols, the research aims to unravel the underlying messages conveyed about the healthcare profession in "Virus." This analysis has the potential to foster a more balanced public perception of healthcare workers in India and globally. Additionally, it highlights how films like "Virus" can employ scientific accuracy to depict the complexities of managing real-world epidemics.